Effect of active vibration control of a circular plate on sound radiation - LENIOWSKA, L. (Archives of Acoustics, 2006)
An active control of the vibration cancellation of a circular fluid-loaded plate is analytically studied. The purpose of this paper is to examine the effect of the active vibration control strategy on the sound radiation generated by a plate. It was assumed that a planar vibrating structure located in a finite baffle and interacting with fluid is driven by a periodic force with constant amplitude. This structure radiates the acoustic waves into a surrounding fluid and a point control force is used to reduce its vibrations. The simulations of the active cancellation of the plate vibrations were made with a Simulink/Matlab computer program. The results demonstrate, that while a control law provided a significant reduction in the plate vibration, it is rather ineffective for noise attenuation.